The time is right for an international PCD disease registry: insight and ongoing research activities. Issue 6 (8th June 2017) - Goutaki, Myrofora; Halbeisen, Florian S.; Kuehni, Claudia E.
We read the editorial entitled "The time is right for an international primary ciliary dyskinesia disease registry" with interest [1]. In it, Haver [1] discussed our recent article on the International Primary Ciliary Dyskinesia Cohort (iPCD Cohort) [2] and stressed three aims important to primary ciliary dyskinesia (PCD) research: the development of a prospective international PCD registry, the standardisation of data collection and the achievement of an international diagnostic consensus. We support these aims and here highlight ongoing activities that support them. It is important to use all available data for PCD research while we strengthen efforts to reach diagnostic consensus http://ow.ly/N7SP30btbVY